2022
DOI: 10.3389/fpsyg.2022.1050214
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of use contexts on user engagement toward tourism short video platforms

Abstract: With tourism short video platforms’ increasingly fierce competition, retaining existing users and improving engagement has taken on greater theoretical and practical significance. Based on the self-system model of motivational development, this study, involving an empirical analysis of 252 user data samples, establishes a research model to determine how the use contexts affect users’ psychological process and finally lead to behavioral engagement. In particular, four use contexts of tourism short video platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The primary focus of the study is to elucidate how TikTok can effectively shape consumer decision-making. Additionally, it identifies research gaps, drawing from prior studies [16,[23][24][25][26][27][28], emphasizing the need for a deeper understanding of the information influencing consumer behavioral intention. These findings serve as the foundation for the primary research question and the development of the research model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary focus of the study is to elucidate how TikTok can effectively shape consumer decision-making. Additionally, it identifies research gaps, drawing from prior studies [16,[23][24][25][26][27][28], emphasizing the need for a deeper understanding of the information influencing consumer behavioral intention. These findings serve as the foundation for the primary research question and the development of the research model.…”
Section: Methodsmentioning
confidence: 99%
“…Kim et al [24] explored how tourism information services impact tourists' perceived enjoyment and their intention to use such services. Recent research has highlighted the potential of UGC on TikTok to engage potential tourists (see [25][26][27]). It has also shown that UGC can influence travel decision-making [16,28].…”
Section: Introductionmentioning
confidence: 99%